Pola Relasi Pemenuhan Nafkah Keluarga Anak Buah Kapal (ABK) Perspektif Teori Kebutuhan Abraham Maslow - Hakim, Mohammad Ainul; Susamto, Burhanuddin; Supriyadi (Maqasid: Jurnal Studi Hukum Islam, 2025)
This study explores the pattern of financial cooperation within the families of fishermen’s crew members (ABK) in Kedungrejo Village, Muncar Subdistrict, Banyuwangi Regency. These families face unstable economic conditions, as the husband's work is affected by seasonal changes, weather, and lunar cycles based on the Javanese calendar. This uncertainty leads to shared financial responsibilities between spouses. The research aims to describe the cooperative relationship between husband and wife in meeting household needs and analyze it using Abraham Maslow’s hierarchy of needs theory. Using an empirical juridical method with a socio-juridical approach, data were collected through interviews and documentation. The findings reveal that the cooperation is influenced by the wife’s willingness to help and the family's unstable financial background. The wife’s involvement is based on awareness, responsibility, and a desire to support family well-being, particularly when fishing activities are halted. Although the husband remains the main provider, the wife plays an active role without neglecting her domestic duties. According to Maslow’s theory, family needs are fulfilled gradually, from basic needs to esteem. However, self-actualization remains unfulfilled due to financial limitations. These families exhibit strong, adaptive partnerships with mutual support, effective communication, and appreciation of each other’s roles.